IMPLEMENTATION OF INCLUSIVE EDUCATION IN KINDERGARTEN LEARNING (CASE STUDY IN PARI CITY, PANTAI CERMIN DISTRICT, SERDANG BEDAGAI DISTRICT) - Parapat, Asmidar; Rozana, Salma; Widya, Rika (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to describe the application of inclusive education to group A kindergarten learning, in Pari City. The object of research is the learning process of group A Kindergarten in Pari City. This study uses a qualitative approach with a case study type of research. Research data obtained through interviews, observation, and documentation. The data collected was analyzed descriptively qualitatively using an interactive analysis model. The validity of the research data was re-tested using extended participation, observation persistence, and triangulation. The results of the study show that inclusive education serves all the needs of students regardless of differences. This can be seen from: (1) class composition consists of various aspects of diversity; (2) each learner gets treatment according to his needs; (3) SPMB is based on the age of the child and there is no test;(4) using an independent curriculum that is tailored to the needs of students; and (5) learning develops aspects: cognitive, language, physical-motor, social-emotional, and moral